Synthesis of Conjugated bis-Schiff Base and Their Complexes as Dye-Sensitizer for Dye Sensitized Solar Cell (DSSC) Application - Nursyafira Adzira, Halmi; Tay, Meng Guan (UNIMAS Publisher, 2022)
Schiff base and their metal complexes have been widely used as photovoltaic materials due to their excellent π-electron transfer properties along the molecule. A total of eleven conjugated symmetrical bis-Schiff base and their complexes with different π-spacers have been synthesized and spectroscopically characterized in order to investigate their conversion efficiency in dye-sensitizer solar cells (DSSC). All compounds were either substituted with hydroxy (-OH) or methoxy (-OMe) as the electron donor and difluoro boron (BF2) as the electron acceptor or without any substituent. All compounds were applied as dye-sensitizer in DSSC using titanium (IV) oxide (TiO2) coated on a fluoride doped tin oxide glass as the working electrode and electric paint containing carbon black, whereas graphene coated indium tin oxide glass as the counter electrode. The power conversion efficiencies of the eleven bis-Schiff bases were compared to N3 Dye as the benchmark standard. The results showed that the compound with aromatic ring bridge as the π-spacer and -OMe substituent gave the highest efficiency at 0.0691% whereas the compound with aromatic ring and BF2 gave the lowest efficiency at 0.0012%.